Assessing the Impact of Competency and Career Growth on Employee Performance: Innovative Work Behavior as a Mediator in Public Sector - Ema Agustina; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Universitas Pendidikan Indonesia, 2025)
This study investigates the impact of competency and career development on employee performance, with innovative work behavior acting as an intervening variable at Bappedalitbang Surabaya. As the primary think tank for the city's development planning, Bappedalitbang requires highly competent human resources to execute its functions effectively. This research aims to analyze the relationships between competency, career development, innovative work behavior, and employee performance. Using a quantitative approach, data were collected through surveys distributed to employees at Bappedalitbang Surabaya. The results indicate that both competency and career development have significant positive effects on innovative work behavior and employee performance. Additionally, innovative work behavior mediates the relationship between competency, career development, and employee performance. These findings provide valuable insights for the Surabaya city government in formulating human resource management policies to enhance employee performance through targeted competency development and career growth initiatives.